Role of CDH1 gene variants and E-cadherin localization in gastric mucosal cancerization - Wu, Yunbo; Zhang, Yunzhan; Dai, Yunkai; Luo, Qi; Lan, Shaoyang; Chen, Xu; Chen, Weijing; Li, Ruliu; Hu, Ling (Frontiers in Oncology, 2025)
BackgroundThis study investigates the role of CDH1 gene single nucleotide polymorphisms (SNPs), mRNA transcription levels, and E-cadherin protein localization in Helicobacter pylori (Hp)-associated gastric diseases and their contribution to gastric mucosal carcinogenesis.MethodsGastric mucosal samples were analyzed for histopathology (Hematoxylin-Eosin staining) and Hp detection (rapid urease test, Giemsa staining). SNPs at the CDH1 gene rs16260 locus were identified via sequencing, mRNA levels were quantified by real-time PCR, and E-cadherin localization was assessed using Elivision™ Plus. Statistical analyses were performed with SPSS 25.0.ResultsParticipants were grouped by gastric mucosal pathology: normal (NOR), gastric inflammation (GI), gastric atrophy (GA), gastric premalignant lesion (GPL), severe dysplasia (GSD), and gastric cancer (GC). No significant differences were found in CDH1 rs16260 genotypes. However, CDH1 transcription was higher in GC compared to NOR and GPL groups. Intestinal metaplasia showed lower CDH1 mRNA levels. E-cadherin expression was higher in GSD and GC compared to other groups. Localization analysis revealed decreased membrane-bound E-cadherin with increased cytoplasmic expression as lesion severity increased. Quantitative analysis showed higher E-cadherin expression in GA than other groups, indicating an initial rise followed by a decline in malignancy. Regression analysis suggested that elevated CDH1 mRNA increased gastric cancer risk, while E-cadherin cytoplasmic ectopic expression heightened the risk of precancerous lesions and gastric cancer.ConclusionThe A allele of the CDH1 gene rs16260 locus show no effect in gastric mucosal pathological evolution, while the elevated mRNA transcription levels potentially increasing the risk of gastric cancer. The loss and ectopic expression of E-cadherin may be significant risk factors for malignant transformation in the gastric mucosa.